Egenföretagande kvinnors försörjningsvillkor och strategier för att minimera försörjningsrisker (Sociologisk Forskning, 2016)
Conditions and strategies for economic security for self-employed women in SwedenAlthough political parties are singing praises of entrepreneurship, welfare systems do not recognize the self-employees’ rights to decent conditions of basic economic safety and oftheir access to social security. This means that self-employed are forced to find their own way to reduce the risks of losing the possibility to support them self economically. This article examines twelve self-employed women’s daily conditions to support themselves and their strategies to deal with risks. The study shows that the interviewed have more freedom to find their own support strategies than wage-employed but on (the other side) their position on the labour market and the systems for social security doesn’t recognize their vulnerability towards risk in the same manner as wage-employed.